2009
DOI: 10.1128/ec.00361-08
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei UDP-Glucose:Glycoprotein Glucosyltransferase Has Unusual Substrate Specificity and Protects the Parasite from Stress

Abstract: In this paper, we describe the range of N-linked glycan structures produced by wild-type and glucosidase II null mutant bloodstream form Trypanosoma brucei parasites and the creation and characterization of a bloodstream form Trypanosoma brucei UDP-glucose:glycoprotein glucosyltransferase null mutant. These analyses highlight peculiarities of the Trypanosoma brucei UDP-glucose:glycoprotein glucosyltransferase, including an unusually wide substrate specificity, ranging from Man 5 GlcNAc 2 to Man 9 GlcNAc 2 glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 71 publications
6
49
0
Order By: Relevance
“…Tunicamycin does inhibit the forward trafficking of other highly glycosylated secretory cargo, such as the lysosomal membrane protein p67 (C. Tiengwe and J. D. Bangs, unpublished observations), but based on our current results, this is apparently not enough to induce a UPR-like response in BSF trypanosomes. Our findings with tunicamycin are consistent with those of Koumandou et al (12) and Izquierdo et al (38), both of whom found no induction of BiP. The latter authors also found that neither heat shock, nor knocking out a component of the ER folding machinery (UDPglucose:glycoprotein glycosyltransferase), affected BiP expression.…”
Section: Discussionsupporting
confidence: 82%
“…Tunicamycin does inhibit the forward trafficking of other highly glycosylated secretory cargo, such as the lysosomal membrane protein p67 (C. Tiengwe and J. D. Bangs, unpublished observations), but based on our current results, this is apparently not enough to induce a UPR-like response in BSF trypanosomes. Our findings with tunicamycin are consistent with those of Koumandou et al (12) and Izquierdo et al (38), both of whom found no induction of BiP. The latter authors also found that neither heat shock, nor knocking out a component of the ER folding machinery (UDPglucose:glycoprotein glycosyltransferase), affected BiP expression.…”
Section: Discussionsupporting
confidence: 82%
“…Glycosyltransferase activity and sugar nucleotides donors have long been linked to protein folding and thermotolerance in many organisms, including different parasites353637. It has been suggested that Protein O -fucosyltransferase 2 (PoFUT2), of which a homolog is conserved and expressed in the P. falciparum genome18, may be involved in a novel quality control mechanism for the proper folding of TSR-domain containing proteins in the endoplasmic reticulum (ER)3738.…”
Section: Resultsmentioning
confidence: 99%
“…In trypanosomatid parasites such as Leishmania and Trypanosoma , sugar-activating enzymes - including UGP - represent attractive drug targets since many vital processes within the parasites utilize UDP-Glc and UDP-Gal38394041. However, drugs targeting structurally conserved elements (i.e.…”
Section: Discussionmentioning
confidence: 99%